Či šiklhā-i gūnāgūnī dārad ʿišq - Ḥaqq Šinās, Muḥammad Ǧawād,Ātišī, Manūčihr (Intišārāt-i Dāstānsarā, 2017)
Commemorative volume, criticism and interpretation on Manūchihr Ātishī
Includes bibliographical references
Keywords: Festschrift; Ātishī; Manūchihr; Persian poetry; Poets; Persian